This is the easy version of this problem. The only difference is the limit of $n$ – the length of the input string. In this version, $1 \leq n \leq 2000$. The hard version of this challenge is not offered in the round for the second division.
Let’s define a correct bracket sequence and its depth as follow:
- An empty string is a correct bracket sequence with depth $0$.
- If “s” is a correct bracket sequence with depth $d$ then “(s)” is a correct bracket sequence with depth $d + 1$.
- If “s” and “t” are both correct bracket sequences then their concatenation “st” is a correct bracket sequence with depth equal to the maximum depth of $s$ and $t$.
For a (not necessarily correct) bracket sequence $s$, we define its depth as the maximum depth of any correct bracket sequence induced by removing some characters from $s$ (possibly zero). For example: the bracket sequence $s = $”())(())” has depth $2$, because by removing the third character we obtain a correct bracket sequence “()(())” with depth $2$.
Given a string $a$ consists of only characters ‘(‘, ‘)’ and ‘?’. Consider all (not necessarily correct) bracket sequences obtained by replacing all characters ‘?’ in $a$ by either ‘(‘ or ‘)’. Calculate the sum of all the depths of all these bracket sequences. As this number can be large, find it modulo $998244353$.
Hacks in this problem in the first division can be done only if easy and hard versions of this problem was solved.Input
The only line contains a non-empty string consist of only ‘(‘, ‘)’ and ‘?’. The length of the string is at most $2000$.Output
Print the answer modulo $998244353$ in a single line.Examplesinput
??
output
1
input
(?(?))
output
9
Note
In the first test case, we can obtain $4$ bracket sequences by replacing all characters ‘?’ with either ‘(‘ or ‘)’:
- “((“. Its depth is $0$;
- “))”. Its depth is $0$;
- “)(“. Its depth is $0$;
- “()”. Its depth is $1$.
So, the answer is $1 = 0 + 0 + 0 + 1$.
In the second test case, we can obtain $4$ bracket sequences by replacing all characters ‘?’ with either ‘(‘ or ‘)’:
- “(((())”. Its depth is $2$;
- “()()))”. Its depth is $2$;
- “((()))”. Its depth is $3$;
- “()(())”. Its depth is $2$.
So, the answer is $9 = 2 + 2 + 3 + 2$.
Solution:
#include <bits/stdc++.h> using namespace std; template <typename T> T inverse(T a, T m) { T u = 0, v = 1; while (a != 0) { T t = m / a; m -= t * a; swap(a, m); u -= t * v; swap(u, v); } assert(m == 1); return u; } template <typename T> class Modular { public: using Type = typename decay<decltype(T::value)>::type; constexpr Modular() : value() {} template <typename U> Modular(const U& x) { value = normalize(x); } template <typename U> static Type normalize(const U& x) { Type v; if (-mod() <= x && x < mod()) v = static_cast<Type>(x); else v = static_cast<Type>(x % mod()); if (v < 0) v += mod(); return v; } const Type& operator()() const { return value; } template <typename U> explicit operator U() const { return static_cast<U>(value); } constexpr static Type mod() { return T::value; } Modular& operator+=(const Modular& other) { if ((value += other.value) >= mod()) value -= mod(); return *this; } Modular& operator-=(const Modular& other) { if ((value -= other.value) < 0) value += mod(); return *this; } template <typename U> Modular& operator+=(const U& other) { return *this += Modular(other); } template <typename U> Modular& operator-=(const U& other) { return *this -= Modular(other); } Modular& operator++() { return *this += 1; } Modular& operator--() { return *this -= 1; } Modular operator++(int) { Modular result(*this); *this += 1; return result; } Modular operator--(int) { Modular result(*this); *this -= 1; return result; } Modular operator-() const { return Modular(-value); } template <typename U = T> typename enable_if<is_same<typename Modular<U>::Type, int>::value, Modular>::type& operator*=(const Modular& rhs) { #ifdef _WIN32 uint64_t x = static_cast<int64_t>(value) * static_cast<int64_t>(rhs.value); uint32_t xh = static_cast<uint32_t>(x >> 32), xl = static_cast<uint32_t>(x), d, m; asm( "divl %4; \n\t" : "=a" (d), "=d" (m) : "d" (xh), "a" (xl), "r" (mod()) ); value = m; #else value = normalize(static_cast<int64_t>(value) * static_cast<int64_t>(rhs.value)); #endif return *this; } template <typename U = T> typename enable_if<is_same<typename Modular<U>::Type, int64_t>::value, Modular>::type& operator*=(const Modular& rhs) { int64_t q = static_cast<int64_t>(static_cast<long double>(value) * rhs.value / mod()); value = normalize(value * rhs.value - q * mod()); return *this; } template <typename U = T> typename enable_if<!is_integral<typename Modular<U>::Type>::value, Modular>::type& operator*=(const Modular& rhs) { value = normalize(value * rhs.value); return *this; } Modular& operator/=(const Modular& other) { return *this *= Modular(inverse(other.value, mod())); } template <typename U> friend const Modular<U>& abs(const Modular<U>& v) { return v; } template <typename U> friend bool operator==(const Modular<U>& lhs, const Modular<U>& rhs); template <typename U> friend bool operator<(const Modular<U>& lhs, const Modular<U>& rhs); template <typename U> friend std::istream& operator>>(std::istream& stream, Modular<U>& number); private: Type value; }; template <typename T> bool operator==(const Modular<T>& lhs, const Modular<T>& rhs) { return lhs.value == rhs.value; } template <typename T, typename U> bool operator==(const Modular<T>& lhs, U rhs) { return lhs == Modular<T>(rhs); } template <typename T, typename U> bool operator==(U lhs, const Modular<T>& rhs) { return Modular<T>(lhs) == rhs; } template <typename T> bool operator!=(const Modular<T>& lhs, const Modular<T>& rhs) { return !(lhs == rhs); } template <typename T, typename U> bool operator!=(const Modular<T>& lhs, U rhs) { return !(lhs == rhs); } template <typename T, typename U> bool operator!=(U lhs, const Modular<T>& rhs) { return !(lhs == rhs); } template <typename T> bool operator<(const Modular<T>& lhs, const Modular<T>& rhs) { return lhs.value < rhs.value; } template <typename T> Modular<T> operator+(const Modular<T>& lhs, const Modular<T>& rhs) { return Modular<T>(lhs) += rhs; } template <typename T, typename U> Modular<T> operator+(const Modular<T>& lhs, U rhs) { return Modular<T>(lhs) += rhs; } template <typename T, typename U> Modular<T> operator+(U lhs, const Modular<T>& rhs) { return Modular<T>(lhs) += rhs; } template <typename T> Modular<T> operator-(const Modular<T>& lhs, const Modular<T>& rhs) { return Modular<T>(lhs) -= rhs; } template <typename T, typename U> Modular<T> operator-(const Modular<T>& lhs, U rhs) { return Modular<T>(lhs) -= rhs; } template <typename T, typename U> Modular<T> operator-(U lhs, const Modular<T>& rhs) { return Modular<T>(lhs) -= rhs; } template <typename T> Modular<T> operator*(const Modular<T>& lhs, const Modular<T>& rhs) { return Modular<T>(lhs) *= rhs; } template <typename T, typename U> Modular<T> operator*(const Modular<T>& lhs, U rhs) { return Modular<T>(lhs) *= rhs; } template <typename T, typename U> Modular<T> operator*(U lhs, const Modular<T>& rhs) { return Modular<T>(lhs) *= rhs; } template <typename T> Modular<T> operator/(const Modular<T>& lhs, const Modular<T>& rhs) { return Modular<T>(lhs) /= rhs; } template <typename T, typename U> Modular<T> operator/(const Modular<T>& lhs, U rhs) { return Modular<T>(lhs) /= rhs; } template <typename T, typename U> Modular<T> operator/(U lhs, const Modular<T>& rhs) { return Modular<T>(lhs) /= rhs; } template<typename T, typename U> Modular<T> power(const Modular<T>& a, const U& b) { assert(b >= 0); Modular<T> x = a, res = 1; U p = b; while (p > 0) { if (p & 1) res *= x; x *= x; p >>= 1; } return res; } template <typename T> bool IsZero(const Modular<T>& number) { return number() == 0; } template <typename T> string to_string(const Modular<T>& number) { return to_string(number()); } template <typename T> std::ostream& operator<<(std::ostream& stream, const Modular<T>& number) { return stream << number(); } template <typename T> std::istream& operator>>(std::istream& stream, Modular<T>& number) { typename common_type<typename Modular<T>::Type, int64_t>::type x; stream >> x; number.value = Modular<T>::normalize(x); return stream; } /* using ModType = int; struct VarMod { static ModType value; }; ModType VarMod::value; ModType& md = VarMod::value; using Mint = Modular<VarMod>; */ constexpr int md = 998244353; using Mint = Modular<std::integral_constant<decay<decltype(md)>::type, md>>; int main() { ios::sync_with_stdio(false); cin.tie(0); string s; cin >> s; int n = (int) s.size(); int l = 0, r = 0, q = 0; for (char c : s) { if (c == '(') ++l; else if (c == ')') ++r; else ++q; } vector<int> pref(n + 1); for (int i = 0; i < n; i++) { pref[i + 1] = pref[i] + (s[i] == '?'); } vector<int> pref_open(n + 1); for (int i = 0; i < n; i++) { pref_open[i + 1] = pref_open[i] + (s[i] == '('); } vector<Mint> fact(n + 1); fact[0] = 1; for (int i = 1; i <= n; i++) { fact[i] = fact[i - 1] * i; } vector<Mint> inv_fact(n + 1); for (int i = 0; i <= n; i++) { inv_fact[i] = 1 / fact[i]; } auto C = [&](int N, int K) { if (K < 0 || K > N) return Mint(0); return fact[N] * inv_fact[K] * inv_fact[N - K]; }; Mint ans = 0; for (int qtor = 0; qtor <= q; qtor++) { int qtol = q - qtor; int x = l + qtol; int y = r + qtor; int lft = pref[y]; int rgt = q - lft; int z = pref_open[y]; for (int k = 0; k <= lft; k++) { ans += C(lft, k) * C(rgt, qtol - k) * (z + k); } } cout << ans << '\n'; return 0; }